2015
DOI: 10.1590/1982-021620154714
|View full text |Cite
|
Sign up to set email alerts
|

Índice de desvantagem para o canto moderno em cantores evangélicos de igrejas tradicionais e pentecostais

Abstract: OBJETIVO:verificar queixas, sintomas vocais e laringofaríngeos e desvantagem vocal de cantores evangélicos, comparando cantores de igrejas tradicionais com cantores de igrejas pentecostais.MÉTODOS:foram analisados 100 cantores evangélicos, de ambos os sexos, divididos em grupos tradicional e pentecostal. Aplicou-se um questionário sobre profissão, autoimagem vocal, queixa, sintomas vocais/laríngeos e o protocolo Índice de Desvantagem Vocal para o Canto Moderno. Os dados obtidos foram analisados estatisticament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
2
0
4
Order By: Relevance
“…The authors of one study (3) that utilized the MSHI and investigated the voice handicap in gospel singers while singing, concluded that amateur church singers presented significant voice handicaps and that, the greater the vocal alteration, the greater the handicap. Another study (14) , which evaluated voice handicaps in gospel singers from traditional and Pentecostal churches using the MSHI procedure, found that the women from the Pentecostal church showed a worse voice handicap index than women from the traditional church. However, research that investigates if the presence of vocal tract discomfort symptoms can affect the voice-related quality of life were not found, given that such symptoms are generally related to excessive use of the voice when singing and to a lack of vocal training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of one study (3) that utilized the MSHI and investigated the voice handicap in gospel singers while singing, concluded that amateur church singers presented significant voice handicaps and that, the greater the vocal alteration, the greater the handicap. Another study (14) , which evaluated voice handicaps in gospel singers from traditional and Pentecostal churches using the MSHI procedure, found that the women from the Pentecostal church showed a worse voice handicap index than women from the traditional church. However, research that investigates if the presence of vocal tract discomfort symptoms can affect the voice-related quality of life were not found, given that such symptoms are generally related to excessive use of the voice when singing and to a lack of vocal training.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies that assess voice handicaps for singing with gospel singers (3,13,14) and the few that do exist are divergent in terms of their findings. One study reports no difference according to gender (3) , while another showed that women presented a higher rate of voice handicap (13) .…”
Section: Introductionmentioning
confidence: 99%
“…Os escores obtidos no IDCM mostram que a subescala Defeito foi a que obteve as piores pontuações na média dos escores e que a subescala Desvantagem a que teve as melhores pontuações. Outras pesquisas com cantores tiveram resultados semelhantes (7,8,11,(25)(26)(27) . Esses resultados indicam que cantores, mesmo que tenham alterações vocais, podem não perceber desvantagem vocal.…”
Section: Discussionunclassified
“…Cantores sem queixas vocais deste estudo tiveram escores muito baixos no IDCM, sugerindo pouca desvantagem vocal. A ausência de queixa vocal também foi relacionada com menor desvantagem em outros estudos (7,8,11,12,(25)(26)(27) . Por outro lado, os cantores com queixas vocais tiveram médias de escores mais altas no IDCM do que em outros estudos que usaram o mesmo instrumento (7,8,11,(25)(26)(27) , exceto em uma pesquisa realizada com cantores com queixas vocais encaminhados para reabilitação (12) .…”
Section: Discussionunclassified
See 1 more Smart Citation